Private Science: Biotechnology and the Rise of the Molecular Sciences - Nancy H. Fontaine (Issues in Science and Technology Librarianship)
This article reviews Private Science: Biotechnology and the Rise of the Molecular Sciences. Arnold Thackray, editor. Philadelphia : University of Pennsylvania Press, c1998, a collection of essays about biotechnology by noted scholars in the fields of history and sociology.